eMERGEing progress in genomics—the first seven years - Crawford, Dana C.; Crosslin, David R.; Tromp, Gerard; Kullo, Iftikhar J.; Kuivaniemi, Helena; Hayes, M. Geoffrey; Denny, Joshua C.; Bush, William S.; Haines, Jonathan L.; Roden, Dan M.; McCarty, Catherine A.; Jarvik, Gail P.; et al. (Frontiers in Genetics, 2014)
The electronic MEdical Records & GEnomics (eMERGE) network was established in 2007 by the National Human Genome Research Institute (NHGRI) of the National Institutes of Health (NIH) in part to explore the utility of electronic medical records (EMRs) in genome science. The initial focus was on discovery primarily using the genome-wide association paradigm, but more recently, the network has begun evaluating mechanisms to implement new genomic information couple to clinical decision support into EMRs. Herein, we describe this evolution including the development of the individual and merged eMERGE genomic datasets, the contribution the network has made towards genomic discovery and human health, and the steps taken towards the next generation genotype-phenotype association studies and clinical implementation.